Rubber tapping machine for plantation industry / Ahmad Syakir Abdul Rahim, Ab Aziz Mohd Yusof and Kamariah Md Isa - Abdul Rahim, Ahmad Syakir; Mohd Yusof, Ab Aziz; Md Isa, Kamariah (School of Mechanical Engineering, 2023)
The process of tapping rubber usually takes a long time and requires awkward positioning. In the long run, rubber tappers might experience backaches especially the elderlies. Rubber tapping machines have been created to facilitate the process. However, these machines are high in cost and are not affordable. Therefore, a new product called "wind-up rubber tapping machine" were developed to overcome this problem. The objective of this project is to design and create a tool that could tap rubber from the rubber tree with a comfortable movement and to fabricate a physical prototype. Several research and observations were made to ensure the success for the specific mechanism to work in the project. This machine is designed to tap rubber from the rubber tree without having to manually estimate the angle of tapping. The front plate already has the direction and angle for the tapping process which is 30 degrees. This makes it easier for beginners who is just learning how to tap rubber. This would also help to test the tapping availability for the tree. As a conclusion, a much easier product to tap rubber were successfully developed and it can help to reduce the burden of rubber tappers